OS DILEMAS DA GESTÃO DE UNIVERSIDADES MULTICAMPI NO BRASIL - Egeslaine de Nez (Universidade Federal de Santa Catarina, 2016)
This research aims to understand the dilemmas of managing the universities multicampi model taking into account that the Brazilian scenario allowed a differentiated model to meet the regions. It is intended to identify the difficulties experienced by this model, drawing on the experience of three decades of existence of the State University of Mato Grosso (Unemat), who has thirteen campus and ten pedagogical cores, indicating alternative ways to overcome obstacles. At first, the methodological procedure was the bibliographic research which consisted in a state of knowledge/state of the art on multicampi terminology. Documentary research on institutional directories and catalogs relating to the topic under study was also used. Later there was a research field applied to five interviews with former pro-rectors for research and post-graduate of the Unemat, besides twenty-one leaders of research groups, providing a depth case study. The approach of reflection data was content analysis and research qualitative/quantitative. Based on these results, it was found that the proposed multicampi expands into smaller units trying not to compromise the institutional identity. You can finally consider that there are advantages in multicampia, however, the geographical dispersion creates administrative difficulties and especially management.